THE INTEGRATION OF BALINESE WISDOM “TRI HITA KARANA” IN PRIMARY STUDENTS’ ENGLISH STORYTELLING PERFORMANCES IN DENPASAR - I Putu Yoga Laksana; I Made Sutajaya; I Wayan Suja; Antari, Wahyu (Yavana Bhasha : Journal of English Language Education, 2025)
In an era of globalization, preserving local cultural values while developing English proficiency presents a significant challenge, particularly in culturally rich regions like Bali, Indonesia. This study explores an innovative approach to addressing this challenge by integrating the Balinese philosophy of Tri Hita Karana (THK) into English language storytelling performances of primary school students in Denpasar. Through qualitative analysis of 40 students’ storytelling performances and in-depth interviews with six competition winners, this research reveals the profound potential of culturally responsive language education. The findings demonstrate that young learners can effectively internalize and creatively express traditional values through a foreign language medium, seamlessly incorporating concepts of parhyangan (human-divine relationship), pawongan (human-human relationship), and palemahan (human-nature relationship) into their narratives. Notably, students displayed a sophisticated ability to apply these ancient principles to contemporary issues, challenging assumptions about the dichotomy between global language acquisition and local cultural preservation. The study uncovers a synergistic model where English becomes a tool for cultural expression and evolution, rather than a threat to traditional values. This approach not only enhances language skills but also deepens cultural understanding and fosters a strong sense of identity. By bridging the gap between global communication needs and local wisdom, this research opens new avenues for developing culturally responsive English language teaching methodologies. The integration of THK in English storytelling performances emerges as a promising model for nurturing linguistic competence, cultural awareness, and creative expression, potentially revolutionizing language education in culturally diverse, non-native English speaking contexts.